A self critique of a decade of injury research by the Injury Control Center Uganda (ICCU). (1st March 2011) - Wandera, B; Nakiito, M; Lett, R
Abstract : Background: The ICCU has been doing injury research, advocacy and training for the last 12 years. Here we provide a review of their findings to provide coherent information and identify priorities areas to tackle. Methods: All original research published between 1999 and 2009 were obtained from the centres records and reviewed. Results: Of the 32 research publications, 15 were original research. The majority were cross sectional (13), while two were longitudinal studies. The burden of injuries in Uganda is 11–15% of the population annually. Road traffic injuries (RTI) contribute 35–50% of all injuries and are the leading cause of injury death among adults although drowning is the leading cause among communities near water bodies, while falls, burns and RTI are the leading causes of injury deaths among children. The Kampala trauma score, with a better utility, was developed and tested for use as a triage tool a grading injury severity. Only 0.09 per capita of government expenditure is put on road safety and emergency and ambulance capacity is very poor. Despite few personnel, trauma team training of emergency medical personnel was done to improve efficiency. Community acceptance of some interventions, like a pedestrian overpass to reduce RTI was low. Conclusion: A lot has been studied about injury in Uganda, however, risk analysis and innovative, injury prevention interventions/management and disability prevention research is needed. A Multi-sectoral approach, increased funding including community participation is needed especially in Road traffic and drowning injury prevention.